Implementation of the Value of Asceticism in the Panji Story to Improve Elementary Student Altruism: A Cultural Approach in Counseling - Hafid, Abd.; Hidayah, Nur; Ramli, M.; Hambali, IM. (International Journal of Psychosocial Rehabilitation, 2020)
This article aims to analyze the implementation of the asceticism value of the Panji story to improve the altruism of elementary school students, which focuses on what the altruism conditions of elementary school students are, to analyze the relationship of the Panji story to the behavior of altruism, and to synthesize the cultural approach of the Panji story asceticism value in counseling. This study uses quantitative descriptive statistical data analysis of each respondent’s item and is discussed through a review and interview analysis literature. Data were obtained from 58 elementary school students in Sumberrejo Bojonegoro District, East Java. The results showed that on average of 58 elementary students, 24 (41%) of them were in the low category. The low altruism of students can be seen in the empathy aspects of 28 students (46.3%), belief on a just world of 23 students (39.66%), social responsibility of 26 students (44.83%), internal locus of control of 20 students (34 , 48%), low egocentrism 20 students (43, 10%). An Indonesian cultural expert considers that the value of asceticism in the Panji story is able to increase one’s altruism to shape the character of the nation, so that the nature, attitudes, and behavior are formed which are more secure for the interests of others than for personal interests.